The Influence of Product Quality and Price on Purchasing Decisions for Fashion Products for Users of the Shopee Marketplace in the Community of Sukagalih Village RT 05 Bandung City - Neng Tika; Doni Dirgantara Asikin (International Journal of Scientific Multidisciplinary Research, 2024)
The purpose of this study was to determine how much influence product quality and price have on purchasing decisions for fashion products on the shopee marketplace in the Sukagalih RT 05 village community. This research method uses associative and descriptive methods. the sample size of this study was 146 respondents where the unit of analysis in this research was shopee marketplace users who had bought fashion products. The analysis technique used is multiple linear regression analysis, besides that, the t-test and F test were also carried out. Based on the results of the study, it shows that product quality partially has a significant effect on purchasing decisions by 35%, while price has an effect of 54% and simultaneously has a significant effect on purchasing decisions for fashion products on the shopee marketplace in the Sukagalih RT 05 village community by 89%. The implication of this research is that there is a need for improvement in the quality of the products offered by the seller and the need for price adjustments to match the actual value of the product. Sellers need to ensure that the price offered reflects the quality and features of the product provided